"Use it or lose it": How online activism moderates the protective properties of gender identity for well-being. (July 2019) - Foster, Mindi D.
Abstract: Regardless of criticisms that online activism does nothing but increase positive feelings, there is merit to understanding the role of online activism for well-being. This research sought to integrate two separate but complimentary lines of research (the well-being effects of activism and social identity) by suggesting that online activism may enhance the ability of social identity to protect against the negative well-being consequences of pervasive discrimination. Three studies, each with different operational definitions of online activism, showed a similar pattern: online activism enhanced the relationship between gender identity and well-being. Consistent with theory on activism's role as a dynamic predictor of social identity (e.g., Drury & Reicher, 1999), this research suggests that online activism, as a means by which social identity can be enacted, can strengthen the protective ability of social identity for well-being. Theoretical and practical implications of the benefits of online activism are discussed. Highlights: Across 3 studies, online activism increased the benefits of gender identity. Analyzing tweets showed female words correlate with well-being words. Pervasive sexism increased gender identity, which increased well-being. These relationships held for those believing online activism is active vs passive. These relationships also held for those participating in online activism vs control.